Spatial Analysis of the Risk of Dengue Hemorrhagic Fever (DHF) at Banyuwangi Regency in 2018 - Firdanis, Dewi; Basuki Notobroto, Hari (Public Health Perspective Journal, 2021)
Dengue Hemorrhagic Fever cases 2018 in Banyuwangi were almost evenly widespread from January to December with the peak of the case in October. In addition, the Case Fatality Rate of Dengue Hemorrhagic Fever in Banyuwangi has also increased compared to the previous years. This study aims to identify areas or sub-districts in Banyuwangi Regency that are at high risk of Dengue Hemorrhagic Fever transmission and obtain information on the risk of an area or sub-district associated with other surrounding areas or sub-districts based on spatial analysis (space effects). This study was nonreactive research that uses a spatial approach to analyze the risk of Dengue Hemorrhagic Fever transmission in an area using GeoDa spatial analysis, including excess risk map and spatial rate map. Areas or sub-districts in Banyuwangi Regency classified as high risk of Dengue Hemorrhagic Fever transmission are Wongsorejo, Banyuwangi, Kabat, and Giri Sub-district. Meanwhile, the sub-districts with a very high risk of Dengue Hemorrhagic Fever when linked with the surrounding sub-districts that intersect or border include the Sub-district of Kabat, Banyuwangi, Giri, Glagah, and Kalipuro. Giri is a sub-district with the highest risk of Dengue Hemorrhagic Fever transmission to the surrounding sub-districts that intersect or border with a rate of 13.4 per 10,000 populations. The benefits of this research are expected to increase knowledge especially in GeoDa spatial analysis, provide information on DHF risk areas, and be used as a reference in making policy efforts related to the risk of DHF transmission.